PERAN BHABINKAMTIBMAS MELALUI BIMBINGAN PENYULUHAN GUNA MENCEGAH TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRES CIREBON KOTA - Arya, Gilang (Advances in Police Science Research Journal, 2020)
ABSTRACT This research is motivated by the high data of vehicle theft cases in the Cirebon City Police jurisdiction. The Republic of Indonesia National Police is making prevention and prevention efforts, one of which is through the connectivity activities in preventing vehicle theft. Therefore, a study was conducted that discussed the general acts of vehicle theft that occurred in the city of Cirebon, the role of Bhabinkamtibmas in order to avoid the crime of vehicle theft, as well as knowing the factors inhibiting the performance of Bhabinkamtibmas. Theories used in this study include management theory, communication theory, routine activity theory, and no-no management. While the concept used is the concept of convention guidance, the concept of community policing, the concept of communication media and the concept of Bhabinkamtibmas. Research conducted by studying qualitative, type of research used is descriptive research, data collection techniques used are interviews, observation, study of documents and research instrument sheets. The results of the study found the vehicle theft case in the Cirebon City Police jurisdiction, mostly in the Cirebon Municipality. The vehicle theft case targets vehicles without dual keys that are parked inside the housing or boarding house. The criminal offense was charged with Article 363 letters 3e, 4e and 5e of the Criminal Code regarding theft by weighting. In implementing guidance and counseling by Bhabinkamtibmas, it has been carried out in accordance with procedures, but there are still a number of factors that hinder the improvement of Bhabinkamtibmas's performance in preventing theft cases. Lack of alacrity in the reduction of theft cases. While the factors that hamper legal factors, law enforcement, society and cultural factors. Research suggestions to optimize the performance of Bhabinkamtibmas (1) provide vocational education and training scheduled for members, (2) carry out analysis and evaluation of routine activities, (3) more supervision in the distribution of inventory items distribution, (4) establish partnerships with the community to create people who are proactive towards police duties, (5) use technology in the community complaints process for Bhabinkamtibmas, (6) give more attention to Bhabinkamtibmas who have a long distance from them home towards their target villages. Keywords: Role, Bhabinkamtibmas, Guidance Counseling, Criminal Acts, Vehicle Theft, Cirebon.